2006
DOI: 10.1021/ja0547477
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structural Elucidation of Azaspiracid-1. Construction of Key Building Blocks for Originally Proposed Structure

Abstract: Syntheses of the three key building blocks (65, 98, and 100) required for the total synthesis of the proposed structure of azaspiracid-1 (1a) are described. Key steps include a TMSOTf-induced ring-closing cascade to form the ABC rings of tetracycle 65, a neodymium-catalyzed internal aminal formation for the construction of intermediate 98, and a Nozaki-Hiyama-Kishi coupling to assemble the required carbon chain of fragment 100. The synthesized fragments, obtained stereoselectively in both their enantiomeric fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…Aldol reaction of ketone 32 and aldehyde 34 gave the coupled adduct 35 in excellent yield as a single diastereomer. On the basis of precedent from us and others,2e, 3e,g we suspected that the C34 stereochemistry was once again incorrect. Fortunately, after removal of the TMS group at C33 and mixed ketal formation at C36, we were able to cleanly invert the C34 stereochemistry using Martin's modified Mitsunobu conditions 12.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Aldol reaction of ketone 32 and aldehyde 34 gave the coupled adduct 35 in excellent yield as a single diastereomer. On the basis of precedent from us and others,2e, 3e,g we suspected that the C34 stereochemistry was once again incorrect. Fortunately, after removal of the TMS group at C33 and mixed ketal formation at C36, we were able to cleanly invert the C34 stereochemistry using Martin's modified Mitsunobu conditions 12.…”
Section: Methodsmentioning
confidence: 91%
“…Fortunately, after removal of the TMS group at C33 and mixed ketal formation at C36, we were able to cleanly invert the C34 stereochemistry using Martin's modified Mitsunobu conditions 12. Staudinger reduction of the azide followed by Teoc protection and cyclization2e using Yb(OTf) 3 gave the HI ring system in 38 . The desired stereochemistry at C34 was confirmed through modified Mosher ester analysis 10.…”
Section: Methodsmentioning
confidence: 99%
“…AZA-2, used for immobilization on the microsphere surface, was synthesized by Nicolaou and co-workers as previously described [5,7,9,26,27]. N -hydroxysuccinimide (NHS), boric acid, bovine serum albumin (BSA), Tween-20, dimethyl sulfoxide (DMSO) and sodium tetraborate decahydrate were obtained from Sigma-Aldrich (Madrid, Spain), and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) was purchased from Pierce (Rockford, Illinois).…”
Section: Methodsmentioning
confidence: 99%
“…HPLC is then used to isolate different AZAs analogs (1)(2)(3)(4)(5) in this sample. Bibliography describes various protocols to achieve this objective, using different columns, flows, temperatures and mobile phases [10][11][12]17,18,[22][23][24][25][26][27].…”
Section: Hplc Separationmentioning
confidence: 99%
“…A new molecule was isolated in extracts from these mussels and named as azaspiracid (AZA1), due to its unusual structure with an azaspiro ring system fused to a 2,9-dioxabicyclo[3.3.1]-nonane ring, a trioxadispiroketal fused to a tetrahydrofuran ring and a carboxylic acid [3]. Synthesis of AZA1 showed that the stereochemistry initially proposed was incorrect and made possible the discovery of the correct structure [4][5][6]. Two analogs of AZA1 (Scheme 1) were isolated in mussels from one of the first toxic episodes and named as azaspiracid-2 (AZA2, 8-methylazaspiracid) and azaspiracid-3 (AZA3, 22-demethylazaspiracid) [7].…”
Section: Introductionmentioning
confidence: 99%